Outlining three arguments for Rights of Antarctica - Baard, Patrik; Mancilla, Alejandra (The Polar Journal, 2024)
In this article, we investigate three arguments for Rights of Antarctica (RoA), understood as recognising the whole continent as a rights-holder with legal standing. For this, we draw inspiration from the Antarctica Declaration, a text developed by an interdisciplinary and international group of scholars and activists. We scrutinise three justifications that could potentially be used in support of RoA. First, we investigate whether arguments for Rights of Nature (RoN) elsewhere can support RoA. RoN has been accepted in several domestic legislations. Unfortunately, we discover important disanalogies between RoA and RoN, defeating the purpose of justifying RoA with reference to RoN. Second, we scrutinise potential arguments that focus on giving rights to specific Antarctic ecoregions or places. However, such arguments would only cover parts of the continent, thus going against the holistic approach of RoA, and they would require using a broader understanding of ?attachments? as grounds for justifying rights for parts of Antarctica. In contrast, we construct an argument for accepting RoA based on four components: (1) Antarctica?s intrinsic value, (2) wider forms of human attachments, (3) Antarctica?s substantial role as a global systemic resource, and (4) the fact that Antarctica is under recurrent and substantial threats. While none of these are individually sufficient for recognising RoA, they can jointly make RoA appropriate. We conclude that it remains an open question whether international law or, more specifically, the Antarctic Treaty, would be open to such conceptual and normative innovation, adopting a new paradigm in our treatment of the nonhuman natural world. At the same time, we hope to kickstart a discussion of what RoA would require and how it should relate more generally to RoN discourses.
Keywords: Antarktis; Antarktistraktaten; jus